Iron triggers TvPI4P5K proteostasis and Arf-mediated cell membrane trafficking to regulate PIP2 signaling crucial for multiple pathogenic activities of the parasitic protozoan Trichomonas vaginalis - Kuan-Yi Wu; Yen-Ju Chen; Shu-Fan Lin; Hong-Ming Hsu (mBio)
ABSTRACT Trichomonas vaginalis is the etiologic agent of trichomoniasis, one of the most common non-viral sexually transmitted infections globally. Our previous work reported the role of phosphatidylinositol 4,5-bisphosphates (PIP2) signaling in the actin-dependent pathogenicity of T. vaginalis. This study further demonstrated that iron transiently regulated T. vaginalis phosphatidylinositol-4-phosphate 5-kinase (TvPI4P5K) proteostasis and its complex formation with an active ADP ribosylation factor TvArf220, facilitating co-trafficking to the plasma membrane, crucial for PIP2 production. In dominant-active HA-TvArf220 Q71L mutant, TvPI4P5K plasma membrane trafficking, PIP2 production, and intracellular calcium levels were increased, while these processes were inhibited in dominant-negative T31N mutant or those by Brefeldin A (BFA) treatment. Additionally, PIP2 replenishment reversed these inhibitions in the T31N mutant, suggesting the critical role of TvArf220 activation in PIP2-calcium signaling. Also, T31N mutant and BFA treatment impaired actin dynamics and cytoskeleton-dependent processes in T. vaginalis, further linking the role of TvArf220 to PIP2-calcium-dependent actin dynamics. Beyond cytoadherence, during host-parasite interactions, TvArf220 influenced both contact-dependent and -independent cytotoxicity, as well as phagocytotic capacity, contributing to the cytopathogenesis of human vaginal epithelial cells. Our findings underscore the key upstream regulation mechanisms of the PIP2 signaling, orchestrating the interplay between TvArf220-PIP2-calcium signaling and downstream actin cytoskeleton-driven pathogenicity in T. vaginalis.IMPORTANCETrichomonas vaginalis actin cytoskeleton-centric pathogenicity is regulated by the phosphatidylinositol 4,5-bisphosphates (PIP2)-triggered calcium signaling cascade in response to environmental iron, though the detailed mechanism by which iron modulates PIP2 signaling remains unclear. Our findings reveal that iron rapidly induces T. vaginalis phosphatidylinositol-4-phosphate 5-kinase (TvPI4P5K) translation followed by its degradation, while simultaneously activating TvArf220 binding, which facilitates TvPI4P5K localization to the plasma membrane for PIP2 production. In contrast to the TvArf220 Q71L mutant, the reduced PIP2 production, intracellular calcium, actin assembly, morphogenesis, and cytoadherence in the dominant-negative T31N mutant were recovered by PIP2 supplementation, indicating the essential role of TvArf220 in PIP2-dependent calcium signaling. Additionally, the contact-dependent or -independent cytotoxicity, along with the phagocytosis, was impaired in the TvPI4P5K- or TvArf220-deficient parasites, as well as in those treated with BAPTA or Latrunculin B. These findings highlight that TvArf220-mediated PIP2-calcium signaling cascade regulates actin cytoskeleton and cytopathogenicity of T. vaginalis. This study uncovers a novel pathogenic mechanism and suggests potential therapeutic targets for parasite control.